Analisis Keterampilan Kolaborasi Siswa pada Pembelajaran IPAS SD - Sufiyah, Faela; Wijaya, Bagus Rahmad (JOURNAL OF EDUCATION FOR ALL, 2024)
The purpose of this study is to analyze collaboration skills in science learning for the 4th grade. This study was conducted using a descriptive quantitative methodology. Thirty primary school pupils served as the research subjects. Utilizing research instruments in the form of interview and observation sheets, data was gathered through interviews and observations. The study's result is that, with an average of each indication ranging from 20 to 50%, research subjects are classified as less and not collaborative. This is a result of the lack of application of collaboration skills, which makes their application essential for developing students' collaborative character.